Nuclear envelope proteins and neuromuscular diseases - Östlund, Cecilia; Worman, Howard J. (Muscle & nerve, 2003)
Several neuromuscular diseases are caused by mutations in emerin and A‐type lamins, proteins of the nuclear envelope. Emery–Dreifuss muscular dystrophy is caused by mutations in emerin (X‐linked) or A‐type lamins (autosomal dominant). Mutations in A‐type lamins also cause limb‐girdle muscular dystrophy type 1B, dilated cardiomyopathy with conduction defect, and Charcot–Marie–Tooth disorder type 2B1. They also cause partial lipodystrophy syndromes. The functions of emerin and A‐type lamins and the mechanisms of how mutations in these proteins cause tissue‐specific diseases are not well understood. The mutated proteins may cause structural damage to cells but may also affect processes such as gene regulation. This review gives an overview of this topic and describes recent advances in identification of disease‐causing mutations, studies of cells and tissues from subjects with these diseases, and animal and cell culture models. Muscle Nerve 27: 393–406, 2003